Workers' Knowledge of their Legal Rights and Resistance to Hazardous Work - Walters, Vivienne; Denton, Margaret (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
The paper presents data from a study of workers' knowledge, perceptions and actions regarding occupational health and safety. The correlates of workers' knowledge of health and safety legislation are analyzed, as well as the links between their knowledge and their resistance to hazardous work. The data suggest that workers who are most disadvantaged in the workplace are least likely to be aware of their rights. The correlates of action regarding health and safety are less clear, though knowledge of the legislation was related to resistance to hazardous work.